EXPLORATION OF THE USE OF AUTOPLAY LEARNING MEDIA IN INCREASING STUDENTS' INTEREST AND LEARNING OUTCOMES IN ISLAMIC EDUCATION SUBJECT AT MA NURUL AKBAR PONGKA, BONE REGENCY - Asrul Asrul; Arisal Arisal; Samsinar Samsinar (Penelitian dan Pengembangan Ilmu, 2025)
This study explores the use of autoplay learning media to enhance student interest and learning outcomes in Islamic Religious Education (PAI) at MA Nurul Akbar Pongka, Bone Regency. Using a qualitative field research design with pedagogical and psychological approaches, data were collected through interviews, observations, and document analysis. Findings reveal that autoplay media facilitates engaging content delivery through integrated text, visuals, audio, and video. Its implementation spanning planning, execution, and evaluation positively influences student interest and supports cognitive, affective, and psychomotor learning outcomes. Supporting factors include adequate facilities and institutional backing, while challenges involve technical limitations and lack of training.